Computational fluid dynamics investigation into flow behavior and acoustic mechanisms at the trailing edge of an airfoil. (January 2018) - Jackson, Beren R; Dakka, Sam M
Airfoil self-noise or trailing edge noise and shear noise were investigated computationally for a NACA 0012 airfoil section, focusing on noise mechanisms at the trailing edge to identify and understand sources of noise production using ANSYS Fluent. A two-dimensional computational fluid dynamics simulation has been performed for 0°, 8°, and 16° airfoil angles of attack capturing surface pressure contours, contours of turbulent intensity, contours of surface acoustic power level, vorticity magnitude levels across the airfoil profile, and x- and y-directional self-noise and shear noise sources across the airfoil profile. The results indicate that pressure gradients at the upper surface do increase as the angle of attack increases, which is a measure of vortices near the surface of the trailing edge associated with turbulence cease as the boundary layer begins to separate. Comparison of the turbulent intensity contours with surface acoustic power level contours demonstrated direct correlation between the energy contributed by turbulent structures (i.e. vortices) and the level of noise measured at the surface and within the boundary layer of the airfoil. As angle of attack is increased, both x and y sources have the same trends; however, y sources (perpendicular to the free-stream flow) appear to have a bigger impact as angle of attack is increased. Furthermore, as the angle of attack increased, shear noise contributes less and less energy further downstream of the airfoil and becomes dominated by noise energy from vortical structures within turbulence. The two-dimensional computational fluid dynamics simulation revealed that pressure, turbulent intensity, and surface acoustic power contours further corroborated the previously tested noise observations phenomena at the trailing edge of the airfoil.